The Role of GLI in the Regulation of Hepatic Epithelial–Mesenchymal Transition in Biliary Atresia - Siyu, Pu; Junxiang, Wang; Qi, Wang; Yimao, Zhang; Shuguang, Jin (Frontiers in Pediatrics, 2022)
Objective: To study the regulatory role of Gli1/Gli2, a nuclear transcription factor of the Sonic hedgehog (Shh) signaling pathway, in epithelial–mesenchymal transition (EMT) related to hepatic fibrosis in patients with biliary atresia (BA). Methods: The messenger RNA (mRNA) and protein expressions of Gli1/Gli2, snail/slug and other Shh- and EMT-related cytokines were tested in liver tissues of BA patients and animals. Then, Gli1/Gli2 was silenced and overexpressed in mouse intrahepatic bile duct epithelial cells (mIBECs) and BA animals to investigate changes in mRNA and protein expression of EMT key factors and liver fibrosis indi-cators. After silencing and overexpression of Gli1/Gli2, immunofluorescence was used to detect the expression of cytokeratin-19 (CK19) and α–smooth muscle actin (α-SMA) in mIBECs, and hematoxylin and eosin (HE) staining and Masson staining were used to observe the degree of liver fibrosis in the BA animals. Results: Compared with the control, the mRNA and protein expressions of Gli2, snail, vimentin and α-SMA were significantly increased, and that of E‑cadherin was signif-icantly decreased, in liver tissue from BA patients and animals. Overexpression of Gli2 increased mRNA and protein expressions of snail, vimentin and α-SMA, and that of E‑cadherin was significantly decreased, in mIBECs and BA animals. After Gli2 silencing, the opposite pattern was observed. Immunofluorescence detection showed enhanced expression of the bile duct epithelial cell marker CK19 in mIBECs after Gli2 silenced, and enhanced expression of the mesenchymal cell marker α-SMA after Gli2 overexpressed. HE and Masson staining suggested Gli2 overexpressed group had a significantly higher degree of fibrosis. Conclusions: The Shh signaling pathway plays an important role in the fibrogenesis of BA. Gli2 can significantly regulate EMT in mIBECs and livers of BA mice.